IMPLEMENTING GAMIFICATION WITH THE PEACEGEN APPLICATION TO ENHANCE STUDENT ENGAGEMENT AND MOTIVATION IN CLASS VII A AT SMPN 1 LABUAPI, WEST LOMBOK: AN ACTION RESEARCH STUDY - Prasetyo, Anggoro Eko; Mubin, Ilmiawan; Anshori, Ahmad; Rukmini, Rukmini (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2023)
Abstract "This classroom action research (CAR) aims to implement gamification strategy using PeaceGen application to enhance the students' learning activity and motivation in 7th grade class A at SMPN 1 Labuapi, West Lombok. The study was conducted for two cycles, involving 30 students as research subjects. The data on students' learning activity and motivation were collected through classroom observation, field notes, and interviews. The results indicate that the implementation of gamification strategy using PeaceGen application can improve the students' learning activity and motivation. In the second cycle, the students' learning activity and motivation significantly increased compared to the previous cycle. Therefore, gamification strategy with PeaceGen application can be an effective alternative method to enhance the students' learning activity and motivation in 7th grade class A at SMPN 1 Labuapi, West Lombok."Keywords: gamification, PeaceGen, student engagement, student motivation, action researchAbstrakPenelitian tindakan kelas (PTK) ini bertujuan untuk menerapkan strategi gamifikasi dengan menggunakan aplikasi PeaceGen untuk meningkatkan keaktifan dan motivasi belajar siswa di kelas VII A SMPN 1 Labuapi, Lombok Barat. Penelitian ini dilakukan selama dua siklus dengan melibatkan 30 siswa sebagai subjek penelitian. Data keaktifan dan motivasi belajar siswa dikumpulkan menggunakan observasi kelas, catatan lapangan, dan wawancara. Hasil penelitian menunjukkan bahwa penerapan strategi gamifikasi menggunakan aplikasi PeaceGen dapat meningkatkan keaktifan dan motivasi belajar siswa. Pada siklus kedua, keaktifan dan motivasi belajar siswa meningkat secara signifikan dibandingkan dengan siklus sebelumnya. Oleh karena itu, strategi gamifikasi dengan aplikasi PeaceGen dapat menjadi alternatif metode yang efektif untuk meningkatkan keaktifan dan motivasi belajar siswa di kelas VII A SMPN 1 Labuapi, Lombok Barat.Kata Kunci gamification, PeaceGen, student engagement, student motivation, action research